Optimizing practice for performance under pressure - Guadagnoli, M. A.; Bertram, C. P. (International Journal of Golf Science, 2014)
The purpose of this paper is to explain the science behind motor skill learning and describe a specific method for optimizing the learning and performance of golf. The Challenge Point Frame work for Motor Learning (Guadagnoli & Lee, 2004) is used as the basis to describe the process of learning a new skill, and is used to describe how this process can be significantly increased, specifically as it pertains to golf. Strategies are prescribed that will serve to enhance the stress-resistant learning that properly planned and executed practice can afford. This paper focuses on the practice method of contextual interference relative to Challenge Point Framework. ABSTRACT FROM AUTHOR